PERKEMBANGAN MODEL PEMBELAJARAN DARI TEMATIK INTEGRATIF MENUJU MERDEKA BELAJAR: IMPLIKASI BAGI PRAKTEK MENGAJAR GURU SD - Sri Ulfa Yunanda (CV. ADIBA ASIHA AMIRA, 2026)
This paper discusses the development of the Islamic Education (PAI) curriculum in elementary schools, focusing on the transformation of learning models from thematic integrative approaches to the Merdeka Belajar framework. The study aims to explore changes in learning concepts, the reorientation of teachers’ roles, and the implications for teaching practices in the classroom. This study uses a literature review method by analyzing relevant books, journals, and official documents related to curriculum development and learning strategies. The findings indicate that the shift toward Merdeka Belajar encourages more flexible, student-centered, and contextual learning processes. Teachers are required to adapt by becoming facilitators, motivators, and guides in the learning process. In addition, teaching practices become more dynamic through the use of varied methods, authentic assessment, and meaningful learning experiences. This transformation is expected to improve the quality of learning and support the development of students' character in a holistic manner.